The relationship between psychological stress and the Motivation Performance In a sample of Students at the Faculty of Education in Damascus University - Al-Assemi, Riadh; Badrieh, Ola (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to investigate the correlated relationship between psychological stress andmotivation PerformanceIn a sample of Students at the Faculty of Education, as well as to investigate the differences according to the gender and academic year.we have usedpsychological stress and motivation Performancescales. The sample was 123 of undergraduate students of the Psychologydepartment. The Concluded results:1-There is a statistically significant correlative relationship between the psychological stress and motivation Performance among the sample’s members.2-There are statistically significant differences among the average students’ performances according to the psychological stress scales, related to gender , in favor of the female members of the chosen sample.3-There are statistically significant differences among the average students’ performances according to the psychological stress scale,related to the academic year variable in favor of the 4th yearstudents.4-There are statistically significant differences among the average students’ performances according to the motivation Performance scales, related to gender, in favor of the female members of the chosen sample.5-There are statistically significant differences among the average students’ performances according to the motivation Performance scale, related to the academic year variable in favor of the 4th yearstudents.